2016
DOI: 10.1007/s12350-015-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

The performance of quantitation methods in the evaluation of cardiac implantable electronic device (CIED) infection: A technical review

Abstract: Quantitation of [F] FDG uptake was found to have a high degree of accuracy in confirming the diagnosis of CIED infection. Normalization to HBP uptake was found to give the greatest AUC and demonstrated excellent reliability. Inconsistencies from published data indicate that individual imaging centers should only use published data for guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The literature search identified a total of 2493 abstracts, and 13 studies met the entry criteria ( Figure 1); no additional eligible studies were identified from the reference lists of studies meeting the inclusion criteria. A total of 11 studies (331 patients, 340 examinations) [12][13][14][15][16][17][18][19][20][21][22] and 2 studies (71 patients, 76 examinations) 23,24 met the inclusion criteria for 18 F-FDG PET-CT and LS, respectively. There were no studies for 67 Ga citrate that met the criteria for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search identified a total of 2493 abstracts, and 13 studies met the entry criteria ( Figure 1); no additional eligible studies were identified from the reference lists of studies meeting the inclusion criteria. A total of 11 studies (331 patients, 340 examinations) [12][13][14][15][16][17][18][19][20][21][22] and 2 studies (71 patients, 76 examinations) 23,24 met the inclusion criteria for 18 F-FDG PET-CT and LS, respectively. There were no studies for 67 Ga citrate that met the criteria for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Peer-reviewed studies investigating the accuracy of 18 F-FDG PET-CT, 67 Ga citrate scintigraphy, or LS for the diagnosis of CIED infection were included. Only studies where sufficient data were provided to calculate true positives, true negatives, false positives, and false negatives were considered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cardiac implantable electronic device lead infection may reflect a different inflammatory disease entity for which late image acquisition in fact appear to be more suitable. [3][4][5] As regards the quantification of the FDG uptake, maximal standard unit value (SUV max) and target-to-background ratio (TBR) between standard and late image acquisition unraveled a great variability in the individual measurements resulting in a wide overlap between both groups with PVE and non-PVE. 1 Such finding emphasizes that even uninfected PHVs may have a certain amount of sterile inflammation, reflecting post-surgical tissue response and/or a mild foreign body reaction depending on the post-interventional period.…”
Section: See Related Article Pp 1960-1967mentioning
confidence: 99%